The use of sugar cane tops for fattening steers in feedlots, supplemented with corn, sorghum, urea and pigeon-pea forage - Thiago, Luiz Roberto L. de S.; Costa, Fernando P.; Silva, José M. da; Baroli, Estelino Augusto; Figueiredo, Geraldo R.; Curvo, João Baptista E. (Pesquisa Agropecuaria Brasileira, 2014)
Using a completely randomized design, 32 crossbred steers averaging 34 months of age and 392 kg of weight received during 100 days sugarcane tops ad libitum and supplementary feeds according to four treatments as follows (figures in DM per head per day): A = 3.6 kg of ground corn grain plus 120 g urea; B = 1.8 kg of ground corn grain plus 3.5 kg of triturated pigeon-pea; C = 3.6 kg of ground sorghum grain plus 120 g urea; and D = 1.8 kg sorghum grain plus 3.5 kg triturated pigeon-pea. Daily sugarcane tops DM intakes and weight gains were respectively: A = 4.65 and 0.381; B = 3.19 and 0.586; C = 4.58 and 0.683 and D = 3.21 and 0.704 kg/head. Consumption of sugarcane tops was reduced only when pigeon-pea was used, independently of the source of grain. The steers that received sorghum gained weight faster (P<0.05) than those consuming corn, and did not occur any significant interaction between sources of grains and sources of protein. All treatments were economically viable being the treatment D the one with the best results.